Assessments of Organic Carbon Stabilization Using the Spectroscopic Characteristics of Humic Acids Separated from Soils of the Lena River Delta - Vyacheslav Polyakov; Evgeny Abakumov (Separations, 2021)
In the Arctic zone, where up to 1024 × 1013 kg of organic matter is stored in permafrost-affected soils, soil organic matter consists of about 50% humic substances. Based on the analysis of the molecular composition of humic acids, we assessed the processes of accumulation of the key structural fragments, their transformations and the stabilization rates of carbon pools in soils in general. The landscape of the Lena River delta is the largest storage of stabilized organic matter in the Arctic. There is active accumulation and deposition of a significant amount of soil organic carbon from terrestrial ecosystems in a permafrost state. Under ongoing climate change, carbon emission fluxes into the atmosphere are estimated to be higher than the sequestration and storing of carbon compounds. Thus, investigation of soil organic matter stabilization mechanisms and rates is quite an urgent topic regarding polar soils. For study of molecular elemental composition, humic acids were separated from the soils of the Lena River delta. Key structural fragments of humic matter were identified and quantified by CP/MAS 13C NMR spectroscopy: carboxyl (–COOR); carbonyl (–C=O); CH3–; CH2–; CH-aliphatic; –C-OR alcohols, esters and carbohydrates; and the phenolic (Ar-OH), quinone (Ar = O) and aromatic (Ar–) groups as benchmark Cryosols of the Lena delta river terrestrial ecosystem. Under the conditions of thermodynamic evolutionary selection, during the change between the dry and wet seasons, up to 41% of aromatic and carboxyl fragments accumulated in humic acids. Data obtained showed that three main groups of carbon played the most important role in soil organic matter stabilization, namely C, H-alkyls ((CH2)n/CH/C and CH3), aromatic compounds (C-C/C-H, C-O) and an OCH group (OCH/OCq). The variations of these carbon species’ content in separated humics, with special reference to soil–permafrost organic profiles’ recalcitrance in the current environment, is discussed.